2015
DOI: 10.1021/acs.est.5b00175
|View full text |Cite
|
Sign up to set email alerts
|

Temporal-Spatial Changes in Viabilities and Electrochemical Properties of Anode Biofilms

Abstract: Sustained current generation by anodic biofilms is a key element for the longevity and success of bioelectrochemical systems. Over time, however, inactive or dead cells can accumulate within the anode biofilm, which can be particularly detrimental to current generation. Mixed and pure culture (Geobacter anodireducens) biofilms were examined here relative to changes in electrochemical properties over time. An analysis of the three-dimensional metabolic structure of the biofilms over time showed that both types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
102
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 187 publications
(120 citation statements)
references
References 42 publications
(137 reference statements)
16
102
2
Order By: Relevance
“…Anodes were polished 1.5 Â 1 Â 0.3 cm graphite plates (4.5 cm 2 surface area) [16] while the cathodes (1.5 Â 1 cm) were made of stainless steel mesh (Type 304, mesh size 90 Â 90).…”
Section: Mecs Construction and Operationmentioning
confidence: 99%
See 3 more Smart Citations
“…Anodes were polished 1.5 Â 1 Â 0.3 cm graphite plates (4.5 cm 2 surface area) [16] while the cathodes (1.5 Â 1 cm) were made of stainless steel mesh (Type 304, mesh size 90 Â 90).…”
Section: Mecs Construction and Operationmentioning
confidence: 99%
“…The viability of pure and mixed culture biofilms can vary within the biofilm, producing different structures: a live outer-layer with a dead inner-core; a dead outerlayer with a live inner-core; and a completely viable biofilm [16,23,24]. So far, most electroactive biofilm studies have reported either completely viable biofilms or biofilms containing a dead inner layer [24e31].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dr. Logan discussed the functional consequence of inactive or dead cells accumulating over time in anode Geobacter anodireducens biofilms. This accumulation results in a two-layer structure with a live outer layer, responsible for current generation, covering an inactive inner core layer that functions as an electrically conductive matrix (37). Howard Stone (Princeton University, Princeton, NJ) showed how particular flow and surface structure influence bacterial biofilm dynamics.…”
Section: Biofilms In Engineered Systemsmentioning
confidence: 99%